2018
DOI: 10.1177/0963662518808729
|View full text |Cite
|
Sign up to set email alerts
|

Why scream about sound in space? The functions of audience discourse about unrealistic science in narrative fiction

Abstract: Sound in space. Featherless dinosaurs. Physics-defying stunts. Unrealistic science in narrative fiction is often a subject of commentary and critique. However, there is limited research investigating the significance, risks and benefits of this discourse for audiences. This article analyses interviews and focus group discussions to develop a typology of functions that are served by audience discourse about the perceived realism of science in fiction. This typology illustrates how discourse about the realism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Looking beyond overall television viewing, some studies have found that genre specific viewing—specifically, science fiction viewing—can influence opinions about science and technology, including biotechnology (Green, 2019; Hamilton, 2003; Nisbet & Goidel, 2007). However, the present study yielded no evidence of a relationship between science fiction viewing and support for uses of gene editing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking beyond overall television viewing, some studies have found that genre specific viewing—specifically, science fiction viewing—can influence opinions about science and technology, including biotechnology (Green, 2019; Hamilton, 2003; Nisbet & Goidel, 2007). However, the present study yielded no evidence of a relationship between science fiction viewing and support for uses of gene editing.…”
Section: Discussionmentioning
confidence: 99%
“…Though cultivation studies initially focused on the impact of overall television viewing, subsequent research has extended the framework to consider the effects of genre-specific media (Potter, 1993; Simis et al, 2015). In the context at hand, the science fiction genre stands out as a potential influence on how audience members form opinions about science and technology (Green, 2019; Hamilton, 2003), including biotechnology (Nisbet & Goidel, 2007). In part, such effects could reflect how popular films and television programs portray scientists as characters.…”
Section: Science Fiction Viewingmentioning
confidence: 99%
“…First, consider science fiction, which has long provided audiences with depictions of science and technology (Green, 2019; Weingart et al, 2003). Though previous research has yielded mixed findings on whether science fiction viewing predicts broad attitudes towards science (Brewer & Ley, 2021; Brossard & Dudo, 2012), studies show that such viewing can predict attitudes toward specific emerging technologies (Besley & Shanahan, 2005; Nisbet & Goidel, 2005).…”
Section: A Framework For Examining Media Use and Attitudes Toward Frtmentioning
confidence: 99%
“…), and media effects (What is the effect of science fiction on science literacy and public attitudes toward science?). In this context, some scientists seek to evaluate or ensure the authenticity of scientific representation in films, and some filmmakers are committed to maintaining verisimilitude (Green, 2019).…”
Section: Introductionmentioning
confidence: 99%